IMPLEMENTATION OF REHABILITATION PROGRAM IN PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFTING IN THE EARLY POSTOPERATIVE PERIOD - Musayev, S.A. (World of Medicine and Biology, 2025)
With the purpose to develop the recovery protocol for the patients undergoing coronary artery bypass grafting 132 patients were observed (30 of them received isolated coronary artery bypass grafting, 30–mitral valve prosthesis, 72–concomitant coronary artery bypass grafting and mitral valve surgery). The rehabilitation program (physical and psychological therapy) was initiated from the first postoperative day (physical therapy within 10–12 days with a further transition to the next stage of rehabilitation during hospital stay). Of the 132 operated patients, only 37 (28 %) had an adequate mental state, 95 (72 %)–significant mental changes: neurosis (20 cases), anxiety-depressive state (49 cases), hypochondria (19 cases), hysteria (7 cases). At the end of the program 121 (91.7 %) patients had an adequate mental state on days 12–14 postoperatively. The mortality was in 8.3 %. The implementation of rehabilitation programs in early period accelerates convalescence period of coronary artery bypass grafting patients.
Keywords: ischemic heart disease; coronary artery bypass grafting; rehabilitation; mitral valve prosthesis; mental disorders